1991
DOI: 10.1002/ddr.430220303
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of picroliv, the active principle of Picrorhiza kurrooa, on rat hepatocytes against paracetamol toxicity

Abstract: Visen, P.K.S., B. Shukla, G.K. Patnaik, S. Kaul, N.K. Kapoor, and B.N. Dhawan: Hepatoprotective activity of picroliv, the active principle of Picrorhiza kurrooa, on rat hepatocytes against paracetamol toxicity. Drug Dev. Res. 22:209-219, 1991. Picroliv, the active principle an iridoid glycoside mixture isolated from the plant Picrorhiza kurrooa, showed dose-dependent (0.75-1 2 mg/kg x 7 days) protective activity on isolated hepatocytes (ex vivo) against paracetamol-induced hepatic damage in rats. It increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Picroliv treatment increases the viability of hepatocytes, suggesting the stabilizing action on hepatic cell membrane by promoting the repair of injured tissues. Picroliv thus showed significant and dose-dependent activity as described earlier in other hepatotoxic models [Visen et al, 1991;Shukla et al, 1992;Dwivedi et al, 1991]. As evidenced by the ED 50 values, picroliv showed a higher hepatoprotective activity than silymarin.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Picroliv treatment increases the viability of hepatocytes, suggesting the stabilizing action on hepatic cell membrane by promoting the repair of injured tissues. Picroliv thus showed significant and dose-dependent activity as described earlier in other hepatotoxic models [Visen et al, 1991;Shukla et al, 1992;Dwivedi et al, 1991]. As evidenced by the ED 50 values, picroliv showed a higher hepatoprotective activity than silymarin.…”
Section: Discussionsupporting
confidence: 59%
“…Isolation of hepatocytes was carried out 24 h post-treatment with rifampicin. The method of Seglen [1975] was followed with slight modification [Visen et al, 1991] for the isolation of hepatocytes by continuously recirculating enzymic perfusion of the liver in situ.…”
Section: Study On Isolated Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of rat hepatocytes and ex vivo studies were performed with slight modification of a previously reported process 21 . The abdomen of the rat was opened under ether anesthesia and heparin (50 units in 0.1 ml) was injected into the heart to prevent blood coagulation.…”
Section: Isolation Of Rat Hepatocytesmentioning
confidence: 99%
“…The plant is well-known in the Ayurveda and has traditionally been used to treat disorders of the liver and upper respiratory tract (Jadhav and Pal, 2005). There are numerous reports about the hepatoprotective activity of Picrorhiza kurrooa and its constituensts kutkin and picroliv (Ansari et al, 1988;Ansari et al, 1991;Visen et al, 1991;Visen et al, 1996;Santra et al, 1998). In addition, the plant and its constituents showed anticholestatic (Saraswat et al, 1993), antioxidant (Govindarajan et al, 2003;Vijayakumar et al, 2005), anti-inflammatory (Singh et al, 1993), cyclooxygenase-2 enzyme inhibitory (Zhang et al, 2005), hypolipidemic (Khanna et al, 1994), and immunomodulatory activities (Wang and Pang, 2002;Vijayakumar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%